Unravelling the intricacies of solvents and sulfur sources in colloidal synthesis of metal sulfide semiconductor nanocrystals - Mauritz, Vincent; Crisp, Ryan (Journal of Materials Chemistry C, 2024)
Synthetic routes producing colloidal metal sulfide semiconductors vary in mechanism depending on the sulfur precursor utilized in the reaction. This review provides overarching insights into the molecular mechanisms underpinning successful material synthesis. The diverse range of sulfur precursors are categorized here into eight general classes representing the most common types of reagents: S8, thioacetamide, thiols, thioethers, dithiocarbamates, carbon disulfide, thioureas, and trialkylphosphine sulfides. These precursors for non-aqueous synthesis provide reactive sulfur species via different pathways to form metal sulfides. The reaction pathways are discussed with a focus on creating quantum-confined colloidal nanocrystals, i.e. quantum dots (QDs), that are applicable as optoelectronic materials. This literature review underscores the nuanced interplay between sulfur source, reaction solvent, and reaction mechanisms, providing insights crucial for tailoring new metal sulfide synthesis strategies<br
CRIS-Team Scopus Importer:2024-08-16